Awareness, Barriers and Intention to Implement Sustainable Construction Among Construction’s Team in Indonesian State-Owned Construction Company - ROHIM, Andri; TANUDJAYA, Yucelline; KARIM, Azwan; ANDRIANI, Ratna (PT Keberlanjutan Strategis Indonesia, 2023)
The construction industry not only has significant impact to Indonesian’s economic development but also to social and environment matters. Sustainable construction is the key to minimize current and future environment and social impact. This paper reports the results of a study about the correlation of sustainable construction (SC) awareness and intentions to implement sustainable construction in one of Indonesian state-owned company. This entails identifying the current status of SC practices, the awareness level of construction teams, the intentions to implement SC, as well as barriers to Implement SC. After comprehensive reviewing the literature, the data is conducted and collected through quantitative approach through questionnaires survey using random sampling techniques. Authors targeted 262 construction teams associated with the Indonesian state-owned construction company as the population and get the feedback as 266 completed questionnaires were received. The data then analyzed through descriptive analysis and Partial Least Square analysis using SmartPLS version 3.9.0. The main findings of this research are as follows: awareness level of SC in Indonesian state-owned construction company is moderate level, and the intention to implement SC is high; awareness has no significant effect for intention to implement SC , So that Indonesian Government should need more campaign and strategies to improve and encourage this concept; in order to be applied efficiently in future projects, it’s because material, competence, cost, and time were found to be the main barrier to implement SC on this study.